ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DENGAN BANK SYARIAH DI INDONESIA - Azizah, Lailatul (universitas Islam Zainul Hasan Genggong, 2024)
This article aims to analyze and compare the financial performance of conventional banks and Islamic banks in Indonesia by using financial ratios, namely liquidity, solvency, profitability, and operational efficiency. This study is based on annual financial report data from several conventional and Islamic banks for the period 2019–2023. The results show that conventional banks tend to perform better in terms of profitability and efficiency, while Islamic banks are better at maintaining liquidity. Factors influencing these performance differences include differences in business models, operational principles, and funding structures.